The environmental and climate dimensions of EU policy towards Asia (Destined to Cooperate? Various Dimensions of European Union Policy Towards Asian Countries, 2024)
Asia is one of the regions in the world most affected by the impacts of climate change and environmental degradation. Meanwhile, the European Union is the most active global actor in promoting environmental protection and combating climate change. The aim of this chapter is to review the EU's environmental policy towards Asian countries. It will present the EU's strategy towards the Indo-Pacific, with a particular focus on environmental protection issues, the main instruments of influence used by the EU, and the major challenges faced by the EU in its environmental and climate actions in Asia. This allows for an answer to the question of what tools the EU uses to fulfill its treaty obligations to combat climate change, and influence partners in Asia. This chapter also serves as an introduction to the second part of the book, which presents three examples of EU-Asian cooperation on environmental and climate issues.